2016
DOI: 10.1002/jssc.201500823
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of 16 polycyclic aromatic hydrocarbons in reclaimed water using solid‐phase extraction followed by ultra‐performance convergence chromatography with photodiode array detection

Abstract: A new fast and effective analysis method has been developed to simultaneously determine 16 polycyclic aromatic hydrocarbons in reclaimed water samples by ultra-performance convergence chromatography with photodiode array detection and solid-phase extraction. The parameters of ultra-performance convergence chromatography on the separation behaviors and the crucial condition of solid-phase extraction were investigated systematically. Under optimal conditions, the 16 polycyclic aromatic hydrocarbons could be sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…The retention behavior in UHPSFC is mainly influenced by the density of the mobile phase, where increase in density leads to a decline in retention and decrease in density leads to an increase in retention . The column temperature and back pressure play an important role in the density and viscosity of the mobile phase; the density and viscosity of the supercritical fluid decrease with an increase in column temperature . In this study, an increase in temperature led to a decline in the density of the CO 2 and thus an increase in retention behavior.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…The retention behavior in UHPSFC is mainly influenced by the density of the mobile phase, where increase in density leads to a decline in retention and decrease in density leads to an increase in retention . The column temperature and back pressure play an important role in the density and viscosity of the mobile phase; the density and viscosity of the supercritical fluid decrease with an increase in column temperature . In this study, an increase in temperature led to a decline in the density of the CO 2 and thus an increase in retention behavior.…”
Section: Resultsmentioning
confidence: 57%
“…14 The column temperature and back pressure play an important role in the density and viscosity of the mobile phase; 17 the density and viscosity of the supercritical fluid decrease with an increase in column temperature. 14,18 In this study, an increase in temperature led to a decline in the density of the CO 2 and thus an increase in retention behavior. The influence of temperature on the retention factors in the Figure S3 (supporting information).…”
Section: Influence Of Temperature and Back Pressurementioning
confidence: 59%
“…e elution extract was concentrated to 1 mL under nitrogen at 30°C. Homogenization of the final extract was achieved with ultrasonic and vortex agitation [19].…”
Section: Sample Preparationmentioning
confidence: 99%
“…Furthermore, the ABR reactor used in the original process is not deep enough and the in uent water is not well-mixed; therefore, the rst grid of the ABR reactor is subjected to a local load greater than the average load, which decreases the treatment e ciency. When Zhao [19] used an "ABR-UASB-biological contact oxidation" process to treat wastewater, the results demonstrated that the removal rates of COD, suspended solid (SS), and NH 3 -N could reach 95.2%, 90.0%, and 71.4%, respectively. In the chemical synthesis pharmaceutical wastewater treatment process, the removal of organic pollutants is generally good, although the concentrations of COD and total nitrogen (TN) in e uent do not reach the standard.…”
Section: Process Improvementmentioning
confidence: 99%
“…PAHs have been determined using GC, GC–MS, HPLC, and UHPLC . Compared with GC and GC−MS, HPLC, or UHPLC is more suitable for the separation of PAHs of high boiling points with isomers included, and has therefore been developed by coupling it to the detectors such as the fluorescence detector (FLD), the diode array detector (DAD), and the UV detector (UVD).…”
Section: Introductionmentioning
confidence: 99%